Molecular Epidemiology of St. Louis Encephalitis Virus, São Paulo State, Brazil, 2016–2018 - Caleiro, Giovana Santos; Claro, Ingra M.; Hua, Xinyi; Basile, Giovana V.; Nuevo, Karolina M.B.; da Costa, Charlys A.; Tubaki, Rosa M.; de Menezes, Regiane M.T.; Scandar, Sirle A.S.; Colebrusco, Lilian A.R.; Araújo, Emerson L.L.; de Souza, William M.; et al. (Emerging infectious diseases, 2025)
We detected St. Louis encephalitis virus (SLEV) in 0.16% (3/3,375) of Aedes and Sabethes spp. mosquitoes captured during 2016-2018 in São Paulo State, Brazil. We also isolated and confirmed that the SLEV strains belong to genotype III. Continued surveillance is required to clarify the burden of SLEV in Brazil.